2020
DOI: 10.1101/2020.06.30.20143560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lockdown measures and relative changes in the age-specific incidence of SARS-CoV-2 in Spain

Abstract: Background: The first months of the SARS-CoV-2 epidemic in Spain resulted in high incidence and mortality. A national sero-epidemiological survey suggests higher cumulative incidence of infection in older individuals than in younger individuals. However, little is known about the epidemic dynamics in different age groups, including the relative effect of the lockdown measures introduced on March 15, and strengthened on March 30 to April 14, 2020 when only essential workers continued to work. Methods: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, during the later strengthened lockdown, older adolescents and younger adults had an increased relative incidence of SARS-CoV-2 infection. 22 Our results, together with these observations, highlight the fact that control measures during a pandemic have differential effectiveness in different age groups.…”
Section: Discussionsupporting
confidence: 60%
“…However, during the later strengthened lockdown, older adolescents and younger adults had an increased relative incidence of SARS-CoV-2 infection. 22 Our results, together with these observations, highlight the fact that control measures during a pandemic have differential effectiveness in different age groups.…”
Section: Discussionsupporting
confidence: 60%
“…It must be noted, though, that the effect of age structure in the infected population under lockdown is still under debate. While the subject has hardly been analyzed in Portugal, there are indications from neighboring Spain that the posterior phases of a lockdown led to an increased proportion of infected adolescents and young adults (12), which may be mirrored in Portugal during the phased easing of the confinement measures. It must be noted that the increase in active cases in Portugal seems to be in line with reports elsewhere after the end of lockdowns, including in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…In scenarios with social distancing we assumed that 80% of cases are symptomatic or can be ascertained [28]. In surveys during the lock-down in the first wave of SARS-CoV-2 in the The Netherlands, it was shown that the daily number of community contacts was reduced by 71% to around 3.7 per day [29] and after the partial lifting of the measures the number of contacts slowly increased again. Similar decreases in contact numbers during the lock-down in the United Kingdom were reported by [30].…”
Section: Social Distancingmentioning
confidence: 99%